FRI0078 Symptom Recognition and Its Effect on Help-Seeking in Rheumatoid Arthritis, Bowel Cancer and Angina: A Mixed Methods Approach. (15th July 2016) - Simons, G.; Belcher, J.; Morton, C.; Kumar, K.; Falahee, M.; Mallen, C.D.; Stack, R.J.; Raza, K.
Abstract : Background: Rheumatoid arthritis (RA) requires treatment in its earliest stages in order to reduce the likelihood of permanent joint damage and disability. However, this therapeutic window is often missed as a result of delayed help-seeking by patients. In order to understand symptom recognition by members of the general public in the context of RA, we conducted two studies which compared symptom recognition and its effect on help-seeking for RA symptoms with symptom recognition in the context of angina and bowel cancer. Objectives: To investigate the role of symptom recognition in the decision to seek appropriate and timely medical attention for RA and other illnesses. Methods: We conducted a qualitative interview study with 31 individuals and a postal survey of 1088 members of the general public. Both studies used vignettes developed specifically for this study describing the symptoms of RA, bowel cancer and angina. In the case of RA one vignette described joint pain and stiffness in hands and wrists; one had joint swelling as an additional feature and we included a variation with symptoms in feet and ankles instead of hands and wrists. For each vignette, participants made causal attributions and rated the seriousness of the symptoms and the urgency with which they would seek medical attention. Results: Participants were less likely to recognise the symptoms of RA than those of other conditions. This effect was more pronounced when the symptoms did not include joint swelling. In contrast, the symptoms of bowel cancer and angina were more readily recognised and were considered to be more serious than those of RA. Survey respondents rated bowel cancer and angina symptoms to be significantly more serious than any of the given combinations of RA symptoms ( Z values of 16.3 to 25.3, all p <0.001). They would also seek help faster for the symptoms of bowel cancer or angina compared to symptoms described in any of the RA vignettes (Z values of 14.7 to 34.2, all p<0.001). Correct causal attribution of symptoms further had more effect on the perceived urgency of help-seeking for angina and bowel cancer than it had for any of the RA vignettes. Conclusions: Accurate symptom attribution and the perception that symptoms are indicative of a serious underlying condition are both important drivers for rapid help seeking. In the case of angina and bowel cancer, recent public health campaigns have promoted not only symptom recognition and seriousness, but have also emphasised the consequences of not seeking timely help. Our results suggest that these consequences should also be addressed in any public health campaign for RA. Acknowledgement: This research is supported by The Dunhill Medical Trust (grant number R226/1111). The authors would also like to thank the interviewees, survey respondents and the patient research partners who have been involved in the development of the research. Disclosure of Interest: None declared